Pocket-hydro turbine into capsule hydro turbine - Azhar, Afif Aiman; Md Shahran, Mohamad Azam; Arifin, Mohamad Nurhakeem; Yahaya, Izat; Abdul Rahim, Ruzairi; Pusppanathan, Jaysuman (Malaysian Society for Computed Tomography & Imaging Technology (MyCT), 2018)
The capsule hydro turbine (CaHT) is a continuous power machine in which a wheel or rotor typically filted whereas produce electricity. It is designed like a capsule shape which has two twin turbines on both output to generate energy as an alternative power supply. The devide is capable of producing output of 12v to power up electrical applicances. The device consist of dynamos, turbines, charging circuit, battery, inverter, and wire cables. The result of the capsule hydro turbine (CaHT) field is presented in three types of graphs as in this paper. The optimum voltage of battery was 6.97v. By using these terms, the research project has successfully improvised the pocket hydro turbine (PHT) into capsule hydro turbine (CaHT)